Effectiveness of Practical Integrative Module in Empowering Family Empowering Family of Children with Cerebral Palsy - Linda Harumi; Eti Poncorini Pamungkasari; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2017)
Bacground: There is a lack of health care services for children with cerebal palsy (CP) in Indonesia. In addition, family of the children with CP are lacking in skills of CP services. A simple, practical, easily readable modul of CP services for families of children with CP has been developed. This study aimed to analyze effectiveness of practical integrative module in empowering family empowering family of children with CP.Subject and Method: This was a quasi experimental study, consisting of intervention and control groups without randomization. The study was conducted at Child Growth Clinic Dr. Soedjarwadi hospital, Klaten, and YPAC, Surakarta, Central Java. A sample of 100 families of children with CP was selected for this study by purposive sampling. The sample was divided into two groups: 50 families in the intervention group and 50 families in the control group. The independent variable was practical integrative module of CP handling, i.e. the intervention under study. The dependent variables were knowledge, attitude, and level of family empowerment in CP services. The data were collected by a set of questionnaire and analyzed by linear regression.Results: After controlling for knowledge before intervention, average knowledge in the intervention group was 0.84 points higher than the control group (b=0.84; 95% CI= 0.33 to 1.86; p = 0.002). The average attitude in the intervention group was 2.48 points higher than the control group (b=2.48; 95% CI= 0.85 to 4.10; p= 0.003). The average level of family empowerment in the intervention group was 3.41 points higher than the control group (b=3.41; 95% CI= 1.34 to 5.48; p = 0.001).Conclusion: The integrative module of CP handling under study is effective in improving knowledge, attitude, and level of family empowerment in families with CP children.Keywords: knowledge, attitude, empowerment, family, cerebral palsy, children, integrative module, cerebral palsy handlingCorrespondence: Linda Harumi. Department of Occupational Therapy, Health Polytechnics, Ministry of Health, Surakarta. Email: lindaharumi@ymail.com. Mobile : +68170628006Journal of Health Promotion and Behavior (2017), 2(2): 173-182https://doi.org/10.26911/thejhpb.2017.02.02.07